IS THE ORGANIZATIONAL LEADERSHIP COMMITTMENT PRINCIPLE THE MOST SIGNIFICANT TQM PRINCIPLE ON HOSPITAL EFFECTIVENESS? - El-Tohamy, Abd El-Moneim A.; Al Raoush, Atef T; Al Doweri, Haetham F; Alkhatib, Ahed J (European Scientific Journal, ESJ, 2015)
Total Quality management (TQM) has many principles, and the objective of this study was to determine highest TQM principle which has the greater impact on overall hospital effectiveness as perceived by healthcare professionals working in accredited governmental hospitals in Jordan. A study survey instrument, designed to measure the impact of applying TQM principles on overall hospital effectiveness, then to find out the greater TQM principle which influence more the overall hospital effectiveness, Study questionnaire was administered to the healthcare professionals in the five governmental accredited hospitals in Jordan, The data collection where 1290 questionnaires. The response rate was 83.6% of the total questionnaires distributed. TQM principles were: Leadership commitment to quality, Customer focus, Continuous improvement, Teamwork, Employee involvement, and education and training. Multiple regression analysis using Beta Coefficient conducted, the result shows that the greater TQM principle which affects the overall hospital effectiveness organization leadership commitment to quality and the least was education and training.